Underwater Target Bearing Detection By Time And Frequency Domain Beamforming - Karakaya, Yilmaz; Gucluoglu, Tansal (IEEE, 2014)
In this paper, underwater target bearing detection performance is investigated with time and frequency domain beamforming. Since dynamic underwater environment is challenging for signal transmission, increasing processing gain and directivity detection success with the use of planar transducer arrays can be helpful especially at low signal powers. In order to understand the effects of use in practical sonar systems better, directivity function of planar array beamforming and performance of with time and frequency domain processing are presented via computer simulations.
Keywords: Beamforming; time domain; frequency domain; underwater bearing detection; Engineering; Telecommunications